Epstein-Barr Virus Early Protein BFRF1 Suppresses IFN-β Activity by Inhibiting the Activation of IRF3 - Wang, Ping; Deng, Yangxi; Guo, Yingjie; Xu, Zuo; Li, Yiwen; Ou, Xiaowen; Xie, Li; Lu, Manjiao; Zhong, Jiayi; Li, Bolin; Hu, Li; Deng, Shenyu; et al. (Frontiers in Immunology, 2020)
Epstein-Barr virus (EBV) is the causative agent of infectious mononucleosis that closely associated with several human malignant diseases, while type I interferon (IFN-I) plays an important role against EBV infection. As we all know, EBV can encode some proteins to inhibit the production of IFN-I, but it’s not clear whether other proteins also take part in this progress. EBV early lytic protein BFRF1 is shown to be involved in viral maturation, however, whether BFRF1 participates in the host innate immune response is still not well known. In this study, we found BFRF1 could down-regulate sendai virus-induced IFN-β promoter activity and mRNA expression of IFN-β and ISG54 during BFRF1 plasmid transfection and EBV lytic infection, but BFRF1 could not affect the promoter activity of NF-κB or IRF7. Specifically, BFRF1 could co-localize and interact with IKKi. Although BFRF1 did not interfere the interaction between IKKi and IRF3, it could block the kinase activity of IKKi, which finally inhibited the phosphorylation, dimerization and nuclear translocation of IRF3. Taken together, BFRF1 may play a critical role in disrupting the host innate immunity by suppressing IFN-β activity during EBV lytic cycle.